The physical health of people with schizophrenia in Asia: Baseline findings from a physical health check programme. Issue 5 (19th April 2016) - Thongsai, S.; Gray, R.; Bressington, D.
Accessible summary: What is known on the subject?: Physical health problems, especially cardiovascular disease and metabolic disorders are far more common in people with severe mental illness (SMI) than the general population. While there are a considerable number of studies that have examined the physical health and health behaviours of people with SMI in Western countries, there have been few studies that have done this in Asia. What this paper adds to existing knowledge?: Unhealthy body mass index (BMI) values were observed in 44% of Thai service users diagnosed with schizophrenia despite desirable levels of exercise and relatively good diets being reported by the majority of participants. Being prescribed two or more antipsychotics was significantly associated with greater body weight and a higher BMI than in people prescribed only one antipsychotic. What are the implications for practice?: Mental health professionals in Asia should be particularly aware of the additional risks of obesity that seem to be associated with antipsychotic polypharmacy when they are promoting the physical health of people with schizophrenia. Abstract: Introduction: People with schizophrenia have worse physical health than the general population, and studies in developed countries demonstrate that their health behaviours are often undesirable. However, as no similar studies have been conducted in Asian countries with emerging healthcare systems, the physical health promotion challenges in these settings is unknown. Aim: To identify and explore relationships between cardiometabolic health risks, lifestyle and treatment characteristics in people with schizophrenia in Thailand. Method: This cross‐sectional study reports the baseline findings from a physical health check programme using the Thai version of the Health Improvement Profile. Results: Despite desirable levels of exercise and relatively good diets being reported by most of the 105 service users, unhealthy body mass index values were observed in 44% of participants. A BMI>23 kg/m² and central obesity was found to be most likely in women. Being prescribed antipsychotic polypharmacy was significantly associated with a higher BMI than in people prescribed monotherapy. Implications for Practice: Mental health professionals in Asia should be aware of the additional risks of obesity that are associated with antipsychotic polypharmacy and may benefit from additional training in order that they may advocate for service users within medication reviews to minimize the potential iatrogenic effects of treatment.